Outcomes of Late-Onset Bleb-Related Endophthalmitis Treated with Pars Plana Vitrectomy - Kazuyoshi Ohtomo; Chihiro Mayama; Takashi Ueta; Miyuki Nagahara (Journal of Ophthalmology)
Purpose. To investigate clinical results on bleb-related endophthalmitis (BRE) after trabeculectomy treated with pars plana vitrectomy (PPV) and to evaluate influence factors for visual prognosis. Methods. Investigating medical records retrospectively, BRE was defined as an endophthalmitis induced by bleb infection. A total of 2018 eyes of 1225 patients who had trabeculectomy between December 2000 and July 2013 were included in this study. Eleven eyes of 11 patients with BRE were performed with PPV. Results. The mean age was 56.6 years. The mean period between trabeculectomy and BRE onset was 7.4 years. The mean period from starting symptom to initiation of treatment for endophthalmitis (PSITE) was 2.3 days. Bleb leakages were observed in 7 eyes (64%). On culture examinations, highly pathogenic bacteria (HPB) were identified in 6 cases (55%). HPB infection was influence factors on visual disturbance (P=.0337). Number of HPB infections is significantly higher in poor visual outcome than without poor visual outcome (P=.0310). Conclusion. Visual prognosis of BRE treated by PPV is significantly better when the pathogenic bacteria are not HPB. Severe visual loss occurred with HPB infection even though patients had appropriate treatments. Physicians need to have careful consideration to prevent bleb infection after trabeculectomy with MMC.